Time-indexed formulation and polynomial time heuristic for a multi-dock truck scheduling problem in a cross-docking centre. (May 2016) - Cota, Priscila M.; Gimenez, Bárbara M.R.; Araújo, Dhiego P.M.; Nogueira, Thiago H.; de Souza, Mauricio C.; Ravetti, Martín G.
Highlights: This work deals with truck scheduling in a cross-docking facility. A time-indexed formulation is proposed and compared against previous models. A polynomial time heuristic is proposed and extensively tested. The heuristic outperformed current results in the literature. Abstract: Cross-docking is a logistic solution bringing significant cost reductions and simplifying operations of distribution centres. The success of this strategy relies on an efficient transhipment operation. This article undertakes a study of truck scheduling in a cross-docking facility. The problem is formulated as a two-stage hybrid flow-shop problem, subject to cross-docking constraints with the objective of minimising the makespan. We propose a time-indexed mixed integer linear programming formulation and a polynomial time heuristic. Results show that the heuristic outperformed current results in the literature for moderate and large size instances.